2018
DOI: 10.14341/probl2017636369-378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular genetic characteristics of MODY1—3 cases in the Russian Federation as shown by NGS

Abstract: Objective — the research was aimed at studying clinical and molecular genetic characteristics of the most common subtypes of MODY (1—3) detected by NGS. Material and methods. The study included 312 patients (162 boys and 150 girls) aged 3 months to 25 years with suspected MODY. Inclusion criteria were as follows: carbohydrate metabolism disorders of varying severity, negative titer of ICA, IA2, and GAD autoantibodies, preserved secretion of endogenous insulin. NGS technique was used for molecular genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the same way, Al-Kandari et al, (15), who studied identification of Maturity-Onset-Diabetes of the Young (MODY) mutations in a Kuwait, reported that the mean age at diagnosis of diabetes was 10.02 (SD ± 5.85) years. Similarly, Zubkova et al, (19), reported that the median age of DM diagnosis in patients with MODY 3 was 10.6 years (0.1; 15 years). However, Zhao et al, (18), reported that age of DM diagnosis in their study was 20.3 years (95% CI: 18.3-22.2).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In the same way, Al-Kandari et al, (15), who studied identification of Maturity-Onset-Diabetes of the Young (MODY) mutations in a Kuwait, reported that the mean age at diagnosis of diabetes was 10.02 (SD ± 5.85) years. Similarly, Zubkova et al, (19), reported that the median age of DM diagnosis in patients with MODY 3 was 10.6 years (0.1; 15 years). However, Zhao et al, (18), reported that age of DM diagnosis in their study was 20.3 years (95% CI: 18.3-22.2).…”
Section: Resultsmentioning
confidence: 79%
“…Similarly, Johansson et al, (20), reported that patients with MODY 3 presents without history of ketosis. While in the study by Zubkova et al, (19), At the disease onset, Three (15.8%) patients had classical signs of diabetes and high hyperglycemia had ketosis in onset. Ketosis is generally believed to be untypical of monogenic forms of DM.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…There are several subtypes of MODY-diabetes, of which MODY2 is the most common in Russia. As of 2021, 50 cases of neonatal diabetes mellitus (1 in 152,280) have been registered in Russia, a molecular genetic study has been performed, however, the prevalence of GCK in Russia remains largely uncertain due to the lack of nationwide screening for diabetes-associated autoantibodies and limited access to molecular genetic testing [7][8][9].…”
mentioning
confidence: 99%
“…MODY2 is milder than other subtypes and is characterized by an asymptomatic course, moderate fasting hyperglycemia, the average level of glycemia is determined in the range of 5.5-8.0 mmol/l, HbA1c often does not exceed the upper limit of normal [8,9]. Such features of the clinical picture in the vast majority of cases lead to erroneous diagnoses, which in turn predetermines an incorrect treatment strategy with negative consequences.…”
mentioning
confidence: 99%